Industrial architecture as a system - Rudenko, Viktor; Rudenko, Taras; Rudenko, Mariia (International Journal of Engineering and Technology, 2018)
It is known that industrial architecture is the important part of modern world. It brings profits and goods to our globalized soÑiety. But industrial facilities is the most susceptible to obsolescence because of dynamics of technical progress development and different economic changes in societies. Industrial architecture, as an independent type of an artificial anthropogenic environment, is about 300 years old. Over the entire period of its existence, it has changed many times, depending on the development of technological progress. The evolution of the ideology of industrial buildings on the territory of Ukraine was uneven with certain jerks. This was facilitated by certain socio-political and military historical events, so Ukraine achieved active industrial development in the -1950-70s. During this period appeared the scientific specialization 18.00.03 "Architecture of Buildings and Structures" which was combined with the specialty 18.00.02 "Architecture of buildings and structures" at the end of this period. From 1961 to 1991 the leading research and design center for industrial buildings was the Scientific Research Institute "TsNIIPromzdaniy", which is located in Moscow. This organization set the direction of development of enterprises to the whole Union (and for Ukraine, which was part of the Union). In the late 1980s, this organization carried out the development of new concepts of industrial enterprises under the state order. During this period a number of concepts of mobile and adaptive industrial enterprises were developed. Adaptive enterprises were introduced in the 90s of the 20th century. But this evolutionary change in the policy of development of industrial enterprises was outstripped by the collapse of the territorial organization of the Union. Â